Potential of Educational Volunteers under Special Education Zones - Kumar, Rajiv (JOURNAL OF INDIAN EDUCATION, 2022)
Education remains inaccessible for millions of children in different pockets of the world. Such pockets could be declared as special education zones (SEZ), where volunteers could play complementary and supplementary roles. Voluntary service in education has been an underutilised domain, particularly for educationally disadvantaged groups. In the post COVID-19 era, this could be a potential tool to bridge the large learning gap which was created due to the lost time of pandemic. Exploratory content analysis method was used to the examine the volunteers. Indian civil service aspirants were taken as the study group, since they seem to be one of the highly motivated individuals to serve the community. This paper found that almost 97 per cent of them were interested in volunteering for education. Education has the ability to shape the next generation and bring a silent revolution for the nation’s development. And, volunteering could become a tool in bringing such revolution at SEZs.